Relationship Between Iron Deficiency Anemia and Stunting in Pediatric Populations in Developing Countries: A Systematic Review and Meta-Analysis - Caroline Oktarina; Charisma Dilantika; Nova Lidia Sitorus; Ray Wagiu Basrowi (MDPI AG, 2024)
Background/Objectives: Iron deficiency anemia (IDA) and stunting are prevalent global health issues, particularly in developing countries, where previous studies have suggested a potential relationship between them. This systematic review aims to analyze the relationship between iron deficiency anemia and stunting in pediatric populations in developing countries. Methods: Literature searches were conducted on PubMed, EMBASE, Cochrane Library, and EBSCO Host. The primary outcome was the association between IDA and stunting. Risk of bias was assessed using the Newcastle-Ottawa Scale (NOS) for cohort studies and the Effective Public Health Practice Project (EPHPP) for other observational studies. Meta-analysis was performed with a random-effects model and heterogeneity assessment. A Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) assessment was performed to determine the certainty and importance of the study. Results: Out of 19,095 articles, 15 studies were included in the systematic review, and 4 studies were included in the meta-analysis, encompassing 21,936 subjects aged 0 to 12 years. IDA prevalence ranged from 3.6 to 58.8%, while stunting prevalence varied from 6.6 to 44.5%. Nine articles supported a significant relationship between IDA and stunting, revealing that stunted children had a 1.31-6.785 times higher risk of developing IDA. The odds ratio of children with IDA to be stunted was 2.27 (95% CI = 1.30-3.95). All studies exhibited a moderate risk of bias. GRADE assessment suggested that the evidence's certainty is low but important. Conclusions: The high IDA prevalence in developing countries, including Indonesia, is associated with stunting in children, suggesting a synergistic relationship.